Fecal Transplant for Treatment of Toxic Megacolon Associated With Clostridium Difficile Colitis in a Patient With Duchenne Muscular Dystrophy. (March 2016) - Yu, Shipeng; Abdelkarim, Ahmed; Nawras, Ali; Hinch, Bryan Thomas; Mbaso, Chimaka; Valavoor, Shahul; Safi, Fadi; Hammersley, Jeffrey; Tang, Jianlin; Assaly, Ragheb
Abstract : Clostridium difficile (C diff) colitis infection is the most common cause of nosocomial infectious diarrhea and the prevalence is increasing worldwide. Toxic megacolon is a severe complication of C diff colitis associated with high mortality. Gastrointestinal (GI) comorbidity and impaired smooth muscle contraction are risk factors for the development of C diff-associated toxic megacolon. We present a case of fulminant C diff colitis with toxic megacolon in a patient with Duchenne muscular dystrophy (DMD) in the intensive care unit. C diff colitis was diagnosed by clinical presentation and positive C diff DNA amplification test (polymerase chain reaction). The impairment of GI tract due to DMD predisposes these patients to severe C diff infection and toxic megacolon, as observed in this case report. For the same reason, the recovery of GI function in these patients can be prolonged. While surgery was conducted for relieving the pressure from toxic megacolon, fecal microbiota transplantation through colonoscopy resulted in successful resolution of the C diff symptoms, although the recovery is prolonged due to DMD.